Entrepreneurial behaviours of final year students at vocational colleges toward interest in entrepreneurship. (28th June 2022) - Saupi, Siti Hajar Nur Atiesa Bt Mohd; Jambari, Hanifah; Noh, Nur Hazirah; Pairan, Mohamad Rasidi; Ahyan, Nurul Aini Mohd.; Ismail, Norulhuda; Taman, Ishak
The research was conducted to study the relationship between entrepreneurial behaviours and the interest in entrepreneurship among the final-year students at a vocational college. These are the main objectives of the investigation: identify the dominant entrepreneurial behaviours; ascertain the correlation between the behaviours and the interest of the students; analyse the students' entrepreneurial behaviours based on the demographic factors; and single out the behaviours that will facilitate cultivation of interest in entrepreneurship. This study adopts the quantitative method using questionnaires as the research instrument. A total of 100 respondents were selected to answer the questionnaires. The SPSS software 18.0 was used to analyse the data. The findings of the research show that the most dominant entrepreneurial behaviour is the career function. In conclusion, the students of the vocational college can become successful entrepreneurs and business people if their entrepreneurial potential is nurtured and they are equipped with the necessary business skills.